Bilateral Trade Analysis of ASEAN and China Countries in ACFTA Cooperation (Gr avity Model Approach): - Devi Tri Wulandari; Lilis Yuliati; Siti Komariyah (Journal Research of Social Science, Economics, and Management, 2022)
At the end of 2001 ASEAN and China agreed on free trade in Bandar Sri Begawan, Brunei Darussalam, known as the ASEAN-China Free Trade Agreement (ACFTA). Periodically, ASEAN and China make agreements, one of the goals of which is to eliminate or cut barriers to trade in goods, both tariffs and non-tariffs. Under ACFTA, tariff reduction began in July 2005 and aims to cut import duties to zero by 2010 on about four thousand types of goods for the relatively developed ASEAN countries namely Thailand, Malaysia, Singapore, Indonesia, the Philippines and Brunei. The Gravity Model predicts trade based on distances and interactions between countries in terms of their economic size. The Gravity Model in economics imitates Newton's law of gravity which also takes into account the physical distance and size between two objects. The application of this model to explain economic phenomena regarding the interaction between the two countries has been widely carried out by economists. The study uses panel data from China and ASEAN6 in the 2010-2020 research period with ASEAN6 exports to China as the dependent variable, and the independent variables include the GDP of the destination country and the country of origin, economic distance proxied in the form of transportation tariffs, exchange rates and economic openness. Panel data regression analysis was used to see the effect of the independent variable on the dependent variable by determining the best model (common effect, fixed effect, random effect) and the classical assumption test performed was the multicollinearity test and the heteroscedasticity test. The results showed that the GDP of destination and origin countries, distance, and exchange rates significantly affected the export value of ASEAN6 to China. Meanwhile, economic openness has no significant effect on the value of ASEAN6 exports to China.